Iron-carbon bond lengths in carbonmonoxy and cyanomet complexes of the monomeric hemoglobin III from Chironomus thummi thummi: a critical comparison between resonance Raman and x-ray diffraction studies. - Yu, N T (1984)
Soret-excited resonance Raman spectroscopy yields direct information regarding the iron-carbon bonding interactions in the cyanomet and carbonmonoxy complexes of hemoglobin III from Chironomus thummi thummi (CTT III) in solution. By isotope exchange in cyanide (13CN-, C15N-, and 13C15N-) and carbon monoxide (13CO, C18O, and 13C18O), we have assigned the Fe(III)-CN- stretching at 453 cm-1, the Fe(III)-C-N- bending at 412 cm-1, the Fe(II)-CO stretching at 500 cm-1, the Fe(II)-C-O bending at 574 cm-1, and the C-O stretching at 1960 cm-1. The resonance Raman data, in conjunction with those obtained from heme model complexes with well-known Fe-C bond distances, strongly suggest that the Fe(III)-CN- bond (approximately 1.91 A) is longer (hence weaker) than the Fe(II)-CO bond (approximately 1.80 A). This result disagrees with those of x-ray crystallographic studies [Steigemann, W. & Weber, E. (1979) J. Mol. Biol. 127, 309-338] in which the Fe-C bond lengths were reported as 2.2 A in cyanomet and 2.4 A in carbonmonoxy CTT III. Based on Badger's rule and normal mode calculations, the x-ray data would lead to the prediction of 279 cm-1 for the Fe(II)-CO stretching frequency in CTT III . CO, which was not observed. On the other hand, we estimate the Fe-CO bond as approximately equal to 1.82 A, which is very similar to the 1.80-A value in human Hb . CO crystals. Furthermore, we have used isotope shift data to estimate the Fe-C-O angle as 169 +/- 5 degrees, somewhat larger than the 161 degrees value found by Steigemann and Weber. We therefore conclude that there must be errors in the x-ray crystallographic refinement for the ligand geometry in carbonmonoxy and cyanomet CTT III.